Ecotourism development innovation in Klaten regency - Anshori, Yuli Tirtariandi El; Enceng, Enceng; Ismiyarto, Ismiyarto (SEAN Institute, 2024)
The development of ecotourism in Indonesia is carried out not only by the government but also by Village-Owned Enterprises (BUMDes). One district, namely Klaten Regency, has 300 BUMDes from 319 villages, and is the largest district that has BUMDes businesses in various categories. Some of these BUMDes focus on developing tourism that utilizes natural wealth or other environmental potential. Tourism development is based on cooperative, participatory, emancipatory, transparent, accountable and sustainable principles. This research study method uses a qualitative descriptive approach. The research objects were 6 (six) villages in Klaten Regency, 3 (three) villages with BUMDes in the advanced category, 2 (two) BUMDes developing, and one BUMDes in the growing category. From the results of research on BUMDes, the principle of transparency is realized starting from budget management, for example at the start of its establishment it produces profits, which are paid as PADes amounting to 30% of the profits from business income and all of this can be accounted for for BUMDes in the advanced category. Meanwhile, BUMDes in the category of growth and development show the principle of transparency starting from the preparation of a master plan for developing business facilities from BUMDes, environmental management and intensifying promotion. Innovation and development of BUMDes that are successful and in the